Diversity, Equity, and Inclusion in Chilean Higher Education - Labraña , Julio; Latorre, Paulina (International Higher Education, 2025)
In Chile, diversity, equity, and inclusion (DEI) have become central to higher education reform in a system long shaped by inequality and market competition. Student movements in 2006, 2011, and 2018 reframed DEI as a condition of institutional legitimacy. Yet regulatory frameworks have often translated DEI into managerial compliance rather than structural change, revealing both the gains and limits of institutionalizing equity.